2011
DOI: 10.1007/s11524-010-9517-6
|View full text |Cite
|
Sign up to set email alerts
|

A Matched-Cohort Evaluation of a Bedside Asthma Intervention for Patients Hospitalized at a Large Urban Children’s Hospital

Abstract: Emergency care and hospitalizations account for 36% of asthma-related medical expenses for children. National asthma guidelines emphasize the need for asthma self-management education at multiple points of care, including the hospital, to help prevent acute exacerbations. The integration of a bedside asthma education program into discharge planning at a busy urban children's hospital aimed to reduce repeat emergency department (ED) visits and hospitalizations by educating the community's highest-risk children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 14 publications
(16 reference statements)
1
28
0
Order By: Relevance
“…29 These results suggest that education provided in the setting of an inpatient stay may further re-enforce key concepts that may potentially play a role in reducing future unscheduled healthcare visits.…”
Section: Discussionmentioning
confidence: 87%
“…29 These results suggest that education provided in the setting of an inpatient stay may further re-enforce key concepts that may potentially play a role in reducing future unscheduled healthcare visits.…”
Section: Discussionmentioning
confidence: 87%
“…Of the studies dealing with patient education interventions, 14/17 studies resulted in beneficial effects as measured by one or several health economic outcomes . Three studies found no health economic impact or effects of the interventions . Use of urgent health care or the frequency of emergency visits, visits to the local doctor and hospitalization, and missed schooldays were frequently investigated in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Use of urgent health care or the frequency of emergency visits, visits to the local doctor and hospitalization, and missed schooldays were frequently investigated in these studies. Use of urgent health care was investigated in 13 studies, and 11 of these found significantly decreased use of urgent health care or trends towards beneficial effects, while two studies found no effects . Of the six studies that had measured hospitalization, three found beneficial effects, while three found no effects .…”
Section: Resultsmentioning
confidence: 99%
“…Studies varied regarding the timing and nature of the intervention components. Eight discharge interventions included a major inpatient component, in addition to outpatient support or follow‐up . Two studies included an inpatient education component only .…”
Section: Resultsmentioning
confidence: 99%